Cylons in America : critical studies in Battlestar Galactica - Potter, Tiffany, 1967-; Marshall, C. W., 1968- (Continuum, 2008)
With its fourth season due to air in January 2008, the award-winning Battlestar Galactica continues to be exceptionally popular for non-network television, combining the familiar features of science fiction with direct commentary on life in mainstream America. Cylons in America is the first collection of critical studies of Battlestar Galactica (its 2003 miniseries, and the ongoing 2004 television series), examining its place within popular culture and its engagement with contemporary American society. Battlestar Galactica depicts the remnants of the human race fleeing across space from a ro.